Enhancement of L-DOPA Production in Micropropagated Plants of two Different Varieties of Mucuna pruriens L., Available in India (Plant Tissue Culture and Biotechnology, 2011)
Reports on increment in L-DOPA content in micropropagated plants, regenerated through a simple technique following shoot bud multiplication in four strains of two different varieties of Mucuna pruriens are made. Nodal segments from in vitro grown seedlings were cultured on modified MS with various concentrations and combinations of BAP, 2iP, Kn either alone or with NAA. Highest shoot regeneration from the callus was achieved in modified MS fortified with BAP at 1.33 µM level. The regenerated shoots were rooted in vitro in half-strength of liquid MS supplemented with various levels of NAA (0.54 - 10.7 mM) or IBA (0.49 - 9.85 mM). However, roots of superior quality were obtained at 5.4 mM NAA level after two weeks in culture. The regenerants were acclimatized for 2 - 3 weeks and about 85% survival rate was observed after transferring to the field. Both chromosome number stability as well as stability in nuclear DNA contents of the regenerants of all these strains was recorded with complete absence of aneuploidy. The different strains have revealed two to three-folds increase in L-DOPA contents in the cultured plants. The L-DOPA concentration in leaves of the regenerated plants varied from11.85 - 15.42 mg/g dry weight in all these accessions. However, the highest amount was observed in the wild strain of M. pruriens. This is the first report on enhancement of L-DOPA content in differentiated tissue of cultured plants of both the varieties of M. pruriens.   Key words: L-DOPA, Micropropagation, Mucuna pruriens, Nuclear DNA   D. O. I. 10.3329/ptcb.v21i2.10224   Plant Tissue Cult. & Biotech. 21(2): 115-125, 2011 (December)